Depth-dependent effects of culling—do mesophotic lionfish populations undermine current management?. Issue 5 (24th May 2017) - Andradi-Brown, Dominic A.; Grey, Rachel; Hendrix, Alicia; Hitchner, Drew; Hunt, Christina L.; Gress, Erika; Madej, Konrad; Parry, Rachel L.; Régnier-McKellar, Catriona; Jones, Owen P.; Arteaga, María; Izaguirre, Andrea P.; et al.
Abstract : Invasive lionfish ( Pterois volitans and P. miles ) have spread widely across the western Atlantic and are recognized as a major threat to native marine biodiversity. Although lionfish inhabit both shallow reefs and mesophotic coral ecosystems (MCEs; reefs from 30 to 150 m depth), the primary management response implemented by many countries has been diver-led culling limited to reefs less than 30 m. However, many reef fish undergo ontogenetic migrations, with the largest and therefore most fecund individuals found at greatest depths. Here, we study lionfish density, body size, maturity and dietary patterns across the depth gradient from the surface down to 85 m on heavily culled reefs around Utila, Honduras. We found lionfish at increased densities, body size and weight on MCEs compared with shallow reefs, with MCEs also containing the greatest proportion of actively spawning females, while shallow reefs contained the greatest proportion of immature lionfish. We then compared lionfish behaviour in response to divers on shallow culled and mesophotic unculled Utilan reefs, and on shallow unculled reefs in Tela Bay, on the Honduran mainland. We found that mesophotic lionfish exhibited high alert distances, consistent with individuals previously exposed to culling despite being below the depth limits of removal. In addition, when examining stomach content, we found that fish were the major component of lionfish diets across the depth gradient. Importantly, our results suggest that despite adjacent shallow culling, MCEs retain substantial lionfish populations that may be disproportionately contributing towards continued lionfish recruitment onto the shallow reefs of Utila, potentially undermining current culling-based management.